Effect Of Dates Consumption On The Increase Of Hb Level On X Grade Female Students At Ma Darul A’mal Metro - Fakhrunnisa Ahmad; Sri Lestariningsih; Gangsar Indah Lestari (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Woman have anemia risk because of monthly period and iron lost about 1,4 mg/day. Anemia incidence on girls in Metro City was about 67%. Presurvey result at Darul A'mal Senior High School showed from 11 students whose Hb level were checked, there were 8 students who had anemia (72.7%). Anemia can be overcome by eating dates. This research aims to know the effect of eating dates to the increase of Hb level on tenth grade female students at Darul A'mal Senior High School Metro. The research used one group pretest posttest from pre-experiment research design. Sample was taken using quote sampling with total of 20 respondents. Data were collected using checklist and mechanical devices (digital Hb). The data were analyzed by univariate analyst using median and bivariate t test dependen on parametric (wiloxon test). The research result obtained median on Hb level measurement before was 11,2 gr/dl and 11,7 gr/dl after. The result of statistic test wilcoxon p value was 0,031. The conclusion of this research, there is an influence of eating dates to the increase of Hb level on tenth grade female students at Darul A'mal Metro Senior High School. It is expected that the students are given dates everyday after taking dawn prayers in congegration or breakfast to prevent and handle anemia at Darul A'mal Senior High School.